Unlocking Luhmann A Keyword Introduction to Systems Theory - Baraldi, Claudio (Transcript Verlag, 2021)
Luhmann's theory is fascinating and complex. It offers incomparably enlightening insights, references and research opportunities, but reveals its utility only after a quite high competence threshold. Using the reticular form of the glossary, this book makes the theory accessible while maintaining its complexity. Without being obstructed by knowledge gaps or by references to concepts presented elsewhere, readers inside and outside sociology get the required support to explore sociological systems theory and to engage with it. Luhmann himself, in his introduction, praises the form of the glossary to cope with the challenges of the theoretical description of our highly complex society.